Street vendors (PKL) household economic sustainability in east Jakarta based on migration status and location trade on time pandemic covid-19 - Beti Nurbaiti; Kemas Ridwan K; Mia Siscawati; Chotib Chotib; I Gusti Agung Ayu Karishma Maharani Raijaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The phenomenon of street vendors (PKL) is not only found in metropolitan cities such as Jakarta in Indonesia as a developing country, but also in big cities in other countries such as Mumbai, Bangkok, Singapore and New York. Street vendors are included in the informal sector which is an alternative source of livelihood for people with limited knowledge, skills and capital.This study aims to analyze the influence between migration status and influence between the types of existing street vendors (Local government-assisted location/Lokbin, Temporary location/Loksem, Base /fixed location/Lapak, and Hawkers/Asongan) to resilience economy House ladder Street vendors. Method study: This is quantitative, using a survey questionnaire of the Central Bureau of Statistics and master plan street vendors DKI. Amount respondents’ study is 420-person street vendors in Jakarta East. Data processed use SPSS with equality regression logistics ordinal. street vendors Which status resident non-risen migrants and non-lifetime migrants are at high economic resilience. street vendors in local government-assisted location chance resilience economy tall than street vendors who are in temporary locations, base/fixed locations, and hawkers). The implication is that street vendors need to be given socialization, education and guidance so as not to disturb the city's public facilities such as pedestrians/trotoar, green spaces, and roadbanks with the existence of sporadic street vendors and hawkers that are aligned with city planning related to spatial planning.